The Flooding Bridge - Abdelhadi, Leila (Stimulus: A Medical Humanities Journal, 2023)
The bridges that connect two sides of the story always merge into one commonality. In this case, it’s the bridge between the doctor and the patient with their family. One side may believe that pursuing an invasive line of procedures will drown the patient in more sorrow and agony, while the other may believe that it’s the only way to save the patient. And the ultimate reality is that they both might be right. A patient could be in a stage where more medical intervention could only do more harm than good, but family intervention might believe it's their duty to keep them alive. A patient could practically on their death bed and their family could be raising the bar to proceed with more medication. A doctor might see no signs of life ahead for a patient and leaving them in hospice would be their only sign of peace at the end of their story. A doctor has watched the patient go through numerous failed trials and seeing them in pain that won't heal, tears them apart. A patient may be tired A patient may be exhausted A patient may be drowning Drowning from the two sides of the bridge flooding to come to an agreement Over the patient and their wants But what does the patient want? What is their wish? What is their need? What is their stance? Sometimes they can't give an opinion, sometimes it's up to the doctors and patient's family. But who’s right? It’s a complicated journey, a complicated question, a complicated answer. Who's right? That’s a question that may never have a definite answer.